Governance styles in Taiwanese universities: Features and effects. (November 2018) - Chan, Sheng-Ju; Yang, Chia-Yu
Highlights: Collegial and bureaucratic models of governance are still dominant and preferred within the universities. However, bureaucratic and corporate styles exercise significantly higher influences upon overall organizational effectiveness at the college level. Taiwan has a dual governance structure inside and outside the university. Abstract: During the past two decades, Taiwan has undertaken dramatic higher education reforms in response to the changing social, economic, and educational needs. Among the driving forces, neoliberalism and new public management (NPM) are major political ideologies in reshaping the configuration, or even nature, of higher education in Taiwan in many aspects. Against this macro context, the study investigated the primary governance styles inside Taiwanese universities. Has the desirable collegiality or collective governance been destabilized or eroded? Our sampled faculty confirms that collegial and bureaucratic models are still dominant and preferred within the universities. While faculty prefer collegial governance, statistical tests have shown that bureaucratic and corporate styles exercise significantly higher influences upon overall organizational effectiveness at the college level. The results suggest that the current reform directions, NPM and neoliberalism, are upheld empirically in Taiwan—these approaches are on right track for better outcomes. Corporate governance is desirable for policy-makers and university senior managers, if universities want to enhance their effectiveness and performance. The study also found that due to inconsistencies between developments at the national and institutional levels, Taiwan has a dual governance structure (inside and outside the university). In addition the study identified a standardized governance pattern in Taiwanese higher education.